Nucleus-Targeting Phototherapy Nanodrugs for High-Effective Anti-Cancer Treatment - Long, Xingyu; Zhang, Xiaojie; Chen, Qiaohui; Liu, Min; Xiang, Yuting; Yang, Yuqi; Xiao, Zuoxiu; Huang, Jia; Wang, Xiaoyuan; Liu, Chong; Nan, Yayun; Huang, Qiong (Frontiers in Pharmacology, 2022)
DNA is always one of the most important targets for cancer therapy due to its leading role in the proliferation of cancer cells. Phototherapy kills cancer cells by generating reactive oxygen species (ROS) and local hyperthermia under light. It has attracted extensive interest in the clinical treatment of tumors because of many advantages such as non-invasiveness, high patient compliance, and low toxicity and side effects. However, the short ROS diffusion distance and local overheating make it difficult for phototherapy to damage DNA deep in the nucleus. Therefore, a very effective strategy to address this bottleneck is nucleus-targeting phototherapy. Recently, some emerging nucleus-targeting phototherapy nanodrugs have demonstrated extremely effective anticancer effects. However, reviews in the field are still rarely reported. Here, we comprehensively summarized recent advances in nucleus-targeting phototherapy in recent years. We classified nucleus-targeting phototherapy into three categories based on the characteristics of these nucleus-targeting strategies. The first category is passive targeting strategy, which mainly targets the nucleus by adjusting the physicochemical characteristics of phototherapy nanomedicines. The second category is to mediate the phototherapy nanodrugs into the nucleus by modifying functional groups that actively target the nucleus. The third category is light-controlled nanodrug into the nucleus. Finally, we provided our own insights and prospects for nucleus-targeting phototherapy nanodrugs. This minireview provides unique insights and valuable clues in the design of phototherapy nanodrugs and other nucleus-targeting drugs.